Bank board structure and loan syndication - Baran, Lindsay; Dennis, Steven A.; Shukla, Maneesh K. (Journal of Banking & Finance, 2025)
We study the impact of bank board structure as a signaling mechanism in loan syndication. We find that the quality of the lead arranger’s board, and specifically the monitoring quality of the board, has a positive effect on the ability to syndicate a loan. The impact of board quality is separate and distinct from lead arranger reputation. Board monitoring quality plays a more important role when the borrower and lead arranger have no prior relationship, after the bankruptcy of an existing borrower, and during the financial crisis. We posit that one channel for our findings is through board oversight of the CEO, and we provide evidence that CEO quality partially mediates the relationship between board quality and loan syndication. Overall, we conclude the quality of the lead arranger’s board, as a separate and distinct effect to reputation, serves as a credible signal to participant banks, mitigating moral hazard and adverse selection concerns.